The Federal Reserve's commercial paper funding facility - Tobias Adrian; Karin Kimbrough; Dina Marchioni (Federal Reserve Bank of New York, 2010)
The Federal Reserve created the Commercial Paper Funding Facility (CPFF) in the midst of severe disruptions in money markets following the bankruptcy of Lehman Brothers on September 15, 2008. The CPFF finances the purchase of highly rated unsecured and asset-backed commercial paper from eligible issuers via primary dealers. The CPFF was a liquidity backstop to U.S. issuers of commercial paper, and its creation was part of a range of policy actions undertaken by the Federal Reserve to provide liquidity to the financial system. This paper documents aspects of the financial crisis relevant to the creation of the CPFF, reviews the operation of the CPFF, discusses usage of the facility, and draws conclusions for lending of last resort facilities in a market based financial system.
Keywords: E44; E58; G18; 330; Federal Reserve; lender of last resort; Commercial Paper; Lender of Last Resort; Finanzmarktkrise; USA